The Transformation of Women’s Roles in Islamic Preaching through the Hermeneutics of Justice on the Conservative Tafseer of the Qur’an in Patriarchal Societies - Fikri Ys, Irsyad Al; Fuad, Asep (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2025)
This study investigates the role of women in contemporary Islamic da’wah as a manifestation of gender role transformation within patriarchal social structures. The urgency of this inquiry stems from the persistent patriarchal bias in scriptural interpretation, which continues to constrain women’s authority and participation in public preaching spaces. Employing a qualitative, library-based approach, the research applies a hermeneutical framework that situates religious texts within their historical, social, and gendered lived contexts. The findings indicate that although women’s engagement in da’wah has expanded through diverse media and public platforms, structural barriers—including discrimination, subordination, marginalization, stereotypes, double burdens, and gender-based violence remain prevalent. The analysis reveals that literalist conservative interpretations tend to perpetuate exclusion, whereas a gender-justice hermeneutical approach reconstructs a more egalitarian understanding of Islam. Compared to prior studies, this research offers novelty by emphasizing the structural and ideological transformation of women’s roles in da’wah. In conclusion, women’s participation in contemporary Islamic da’wah represents a strategic repositioning, reinforced by contextual reinterpretation of religious texts, thereby expanding their legitimacy and contributions as agents of spiritual and social change.